Modified starches and their usages in selected food products:a review study. - Abbas, Kassim Ali; K. Khalil, Sahar; Meor Hussin, Anis Shobirin (Canadian Center of Science and Education, 2010)
Modified starches have been developed for a very long time and it applications in food industry are really significant nowadays. This paper will elaborate more about the definition and classifications of modified starches by considering several modification techniques such as physical, chemical, and enzymatic treatment. Review on journal’s papers of current decade has been done so as to observe the latest applications of modified starches in the food industry. In order to organize the findings, they have been divided into several sub-groups according to its functional applications, as fat replacer/fat mimetic, as texture improver, for high nutritional claim, for high shear and temperature stability, and for flavor oil encapsulation. Examples on its recent applications of specificfoods products were also included. Hopefully this paper will assist anyone especially students who wants to get information about the latest applications of modified starch in the food industry.